Development of novel lubricant formulation for cleanroom and vacuum application - Fabian Schüler; Andreas Keller; Markus Grebe; Anthony Kent; Michael Buttery; Malgorzata Holynska (Scientific Reports)
Abstract Contamination sensitive applications are processes in various industries that require extremely controlled conditions, and which are conducted in dedicated cleanrooms or in cleanroom-like environments. Process cleanliness and quality can further be enhanced by employment of vacuum, like in semiconductor or medical device manufacturing, or it is inevitably present as in some space applications. Such environments impose unique demands on materials from two perspectives – performance and cleanliness. To meet the comprehensive set of requirements, the development approaches diverge from conventional methods and strategies for material development. In this article, the specific area of lubricants in cleanroom and vacuum and its impact on their development will be discussed. Firstly, the implications of vacuum and cleanroom requirements on lubricants will be discussed. An overall development methodology and the specific validation and qualification methods will be presented, and insights into material selection and formulation development will be provided.